2004
DOI: 10.1590/s0037-86822004000700002
|View full text |Cite
|
Sign up to set email alerts
|

Infecção pelos vírus das hepatites B e D entre grupos indígenas da Amazônia Brasileira: aspectos epidemiológicos

Abstract: Several studies describe very high prevalence rates of infection and disease of hepatitis B and D within Native American population. This is a review of what has been described among Amerindians of Brazilian Amazon. Some groups show low prevalence rates of HBsAg, whereas, others of the same region reveal high endemic pattern, even among individuals less then 10 years of age. HDV is only found in groups of Amazonas province. Transmission may occur by interfamilial dissemination or sexual contact among young adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 26 publications
0
10
0
5
Order By: Relevance
“…Among the indigenous population of the Western Amazon, serum epidemiological studies reported prevalence rates of chronic carriers above 20% 8,11 .…”
Section: Methodsmentioning
confidence: 99%
“…Among the indigenous population of the Western Amazon, serum epidemiological studies reported prevalence rates of chronic carriers above 20% 8,11 .…”
Section: Methodsmentioning
confidence: 99%
“…A infecção pelo VHB é endêmica na América do Sul e sua prevalência é particularmente alta na Amazônia, inclusive entre as populações indígenas (14,15,20,21). De um modo geral, a infecção pelo VHB é considerada de alta endemicidade em regiões onde a prevalência do AgHbs é superior a 7% e mais de 60% da população têm evidência sorológica de infecção prévia.…”
Section: Anti-hbsunclassified
“…A vacinação contra o VHB foi então iniciada em Lábrea, em setembro de 1989, na tentativa de deter a doença, logo estendida a mais dez municípios dos rios Purus (Canutama, Pauiní, Tapauá e Boca do Acre), Juruá (Eirunepé, Carauari, Itamarati e Envira) e médio Solimões (Coari e Codajás). Foram vacinadas, sob a organização daquela campanha, crianças de até nove anos de idade e profissionais de saúde, com três doses de vacina DNA recombinante que, passou a fazer parte do calendário de vacinação em todo do Estado de Amazonas, a partir de 1992 (Braga et al, 2004).…”
Section: A Hepatite Delta Na Amazôniaunclassified
“…em Itamarati e 15,5% em Codajás. A prevalência de anti-HBc total (anticorpos contra o antígeno do "core" do VHB) alcançava taxas bastante elevadas, como 52,1% em Lábrea, 71,4% em Itamarati e 62,5% em Codajás; e as taxas de prevalência do VHD em indivíduos com reatividade para o HBsAg era relatada em torno de 32% (Braga et al, 2004).…”
Section: A Hepatite Delta Na Amazôniaunclassified
See 1 more Smart Citation